Economic Uncertainty, Parental Selection, and the Criminal Activity of the 'Children of the Wall' - Arnaud Chevalier; Olivier Marie (Institute for the Study of Labor (IZA), 2013)
We explore the link between parental selection and criminality of children in a new context. After the collapse of the Berlin Wall in 1989, East Germany experienced a very large, but temporary, drop in birth rates mostly driven by economic uncertainty. We exploit this natural experiment in a differences-in-differences setup to first estimate that the children from these affected (smaller) cohorts are relatively much more likely to be criminally active. Using individual level data, we provide evidence that women who gave birth in at this period of uncertainty were negatively selected into fertility. Further investigation of the underlying mechanisms reveals that emotional attachment and intergenerational transmission of risk attitudes play important roles in the parental selection-crime of children relationship. Finally, results for siblings support a causal interpretation of our findings.
Keywords: J13; K42; 330; crime; parental selection; fertility decision; economic uncertainty; risk attitude